2011
DOI: 10.1186/1532-429x-13-58
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance myocardial feature tracking detects quantitative wall motion during dobutamine stress

Abstract: BackgroundDobutamine stress cardiovascular magnetic resonance (DS-CMR) is an established tool to assess hibernating myocardium and ischemia. Analysis is typically based on visual assessment with considerable operator dependency. CMR myocardial feature tracking (CMR-FT) is a recently introduced technique for tissue voxel motion tracking on standard steady-state free precession (SSFP) images to derive circumferential and radial myocardial mechanics.We sought to determine the feasibility and reproducibility of CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 24 publications
6
100
2
3
Order By: Relevance
“…For feature tracking at 1.5T,16 an interobserver coefficient of variation between 5.48% and 17.3% was reported for longitudinal strain, and between 4.9% and 13.3% for circumferential strain. For feature tracking at 3.0T, an interobserver coefficient of variation between 16.3% and 26.4% for longitudinal strain and between 9.9% and 20.3% for circumferential strain17, 18, 29, 30 was reported. Reproducibility with DENSE is higher than with Tagging 30.…”
Section: Discussionmentioning
confidence: 99%
“…For feature tracking at 1.5T,16 an interobserver coefficient of variation between 5.48% and 17.3% was reported for longitudinal strain, and between 4.9% and 13.3% for circumferential strain. For feature tracking at 3.0T, an interobserver coefficient of variation between 16.3% and 26.4% for longitudinal strain and between 9.9% and 20.3% for circumferential strain17, 18, 29, 30 was reported. Reproducibility with DENSE is higher than with Tagging 30.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Reference values for LV circumferential, radial and longitudinal strain have been published recently. 30,31 Assessment of ventricular deformation at rest and with inotropic stimulation using dobutamine has provided clinically relevant data in health 18,20 and disease states. 23, 24 Schneeweis et al 23 demonstrated the ability to use circumferential short-axis strain to identify inducible ischemia during intermediate and high-dose dobutamine stimulation.…”
Section: Ventricular Performancementioning
confidence: 99%
“…The technique can be applied for the quantification of right and left ventricular (LV) systolic and diastolic function using strain 10,18 and SR 19 imaging as well as myocardial torsion and diastolic recoil quantification. 20,21 The study of atrial physiology using strain and SR imaging has recently been explored.…”
Section: Quantitative Assesment Of Cardiovascular Physiologymentioning
confidence: 99%
“…Late gadolinium-enhanced cardiovascular magnetic resonance (LGE-CMR) was performed in identical slice orientations using conventional methods with a repetition time of 4.9 ms, echo time of 2.4 ms, flip angle of 15°, and spatial resolution at 1.7×1.7×8 mm 3 . Post-processing of perfusion images was performed with dedicated software (Circle Cardiovascular imaging Suite 12, Release 3.4.0 (84) Calgary, Alberta, Canada) and a dedicated feature tracking prototype software (Diogenes MRi, Tomtec, Germany) [14].…”
Section: Cmr Imagingmentioning
confidence: 99%